PROFESSIONALLY-ORIENTED CONTEXT OF THE DEVELOPMENT OF SELF-EDUCATIONAL COMPETENCE OF TEACHERS IN THE MASTER’S DEGREE PROGRAMME SETTINGS - Бобрицька, В. І. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2015)
In the article there has been substantiated the relevance of the research of the problem of the development of self-educational competence of the tertiary teachers to be in the Master’s degree programme settings. Based on the analysis of scientific approaches to the interpretation of the subject-matter of the notions «self-education», «competence», there has been specified the concept of «self-educational competence of a tertiary teacher to be». There has been generalised both domestic and foreign best practice, which is the theoretical basis for the study on the formation of self-educational competency of a teacher to be for a modern higher educational institution in the settings of Master’s degree programme. There have been specified organizational and pedagogical prerequisites of the development of self-educational competence of the graduates of the Master’s degree programme as the system of educational process organization in higher education is being reformed